Gospodarstwo rolne (zbożowe) w Unii Europejskiej - bilans kosztów i korzyści - Brodzińska, Katarzyna (Corn Farm in the European Union - Balance of Costs and Profits, 2005)
The aim of this paper is to find out the impact of direct payments on farms competitivess. Price relation between corn and means of production in 2004 caused only a partial compensation of farmer's income in proportian to direct payments. The gross margin shows that the direct payments system can make rural production more extensive.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 78-83